Step-by-step explanation:
i think its 4.2m^2+1.5n
Answer:
4.2m^2+1.5n
Step-by-step explanation:
1.7m^2 + 6.5n - 4n + 2.5m^2 - n
First, rearrange the numbers so that they can be added or subtracted with their like terms.
It would look like this:
(1.7m^2 + 2.5m^2) + (6.5n - 4n - n)
All you have to do is solve from here
this would simplify into:
4.2m^2+1.5n
Hope this helped!
The original price of a skateboard was reduced by $15. The new price is $49.
Answer:
The original price of a skateboard is $64
Step-by-step explanation:
Let
x ----> the original price of a skateboard
y ----> the new price of a skateboard
we know that
The linear equation that represent this problem is equal to
y=x-15 ----> equation A
y=49 ---> equation B
substitute equation B in equation A and solve for x
49=x-15
Adds 15 both sides
49+15=x
64=x
Rewrite
x=$64
PLEASE HELP ASAP If mZYWZ - 17, what is mw
?
34
73
56
17
Answer:
73°
Step-by-step explanation:
Since WX = WZ then ΔWXZ is isosceles and WY is perpendicular to XZ
Hence ∠XYW = 90°
YW bisects XWZ, hence ⇒ ∠ YWX = ∠YWZ = 17°
The sum of the 3 angles in ΔWXY = 180°, hence
∠WXY = 180° - (90 + 17)° = 180° - 107° = 73°
Jennifer stores her fishing pole in a cylindrical case. The cylinder has a diameter of 5 inches and a height of 50 inches.Which is closest to the volume, in cubic inches, of the cylinder?
Answer:
Volume of Cylinder = 981.75 cubic inches
Step-by-step explanation:
There is no answer choice shown, but i will answer this using formula for volume of cylinder and round the answer to 2 decimal places.
You match it with the choices that u have.
The volume of a cylinder is given by the formula [tex]V=\pi r^2 h[/tex]
Where
V is the volume
r is the radius (half of diameter)
h is the height
We know diameter is 5, so radius is 2.5
also, the height is 50
We simply plug it in the formula and solve:
[tex]V=\pi r^2 h\\V=\pi (2.5)^2 (50)\\V=981.75[/tex]
The length of a rectangle exceeds its width by 3
inches, and the area is 54 square inches. What
are the length and width of the rectangle?
Answer:
The length is 9 and the width is 6.
Step-by-step explanation:
6*9 = 54 and 9 is 3 greater than 6.
After graduating from college, Carlos receives two different job offers. Both pay a starting salary of
$62000 one job promises a $3720 raise per year. What will the salary be in one year
Answer:
$65720
Step-by-step explanation:
The job pays a starting salary of $62000, and raises $3720 per year. In one year, Carlos will be earning $62000 + $3720 = $65720
Final answer:
Carlos's salary in one year will be $65720, which is the sum of his starting salary, $62000, and the promised annual raise of $3720.
Explanation:
After graduating from college, Carlos has received two different job offers, both offering a starting salary of $62000, and one includes a promise of a $3720 raise per year. To calculate his salary in one year, we need to add this annual raise to his starting salary.
Starting salary: $62000
Raise after one year: $3720
Carlos's salary in one year: $62000 + $3720 = $65720
This computation shows that with the promised annual raise, Carlos's salary for the next year would be $65720.
If g(x) = xsquared +2, find the g (3)
Answer:
g(3)=11 I think
Step-by-step explanation:
Since x is 3, you substitute it in for the x. So it would be 3 squared +2.
I'm not sure if this is right but I tried helping.
Answer:
g(3) =11
Step-by-step explanation:
g(x) = x^2 +2
Let x =3
g(3) = 3^2 +2
= 9+2
= 11
Factor each expression. Show your work. 11. r2 + 12r + 27 12. g2 – 9 13. 2p3 + 6p2 + 3p + 9
Answer:
11. r^2 + 12r + 27 = (r+3)(r+9)
12. g^2-9 = (g+3)(g-3)
13. 2p^3 + 6p^2 + 3p + 9 = (2p^2+3)(p+3)
Step-by-step explanation:
[tex]11.\ r^2 + 12r + 27\\Factorizing\\= r^2+9r+3r+27\\=r(r+9)+3(r+9)\\=(r+3)(r+9)\\\\12. g^2-9\\The\ expression\ will\ be\ factorized\ using\ the\ formula\\(a+b)(a-b)=a^2-b^2\\So,\\g^2-9\\=(g)^2-(3)^2\\=(g+3)(g-3)\\\\13. 2p^3 + 6p^2 + 3p + 9\\=2p^2(p+3)+3(p+3)\\=(2p^2+3)(p+3)[/tex] ..
Complete the table for the given rule y=x-3
For the first row, where x is equal to 7, to find y plug 7 in for x like so...
y = 7 - 3
y = 4
For the second row, where y is equal to 1, to find x plug 1 in for y like so...
1 = x - 3
To solve for x add 3 to both sides. This will cancel 3 from the right side:
1 + 3 = x - 3 + 3
4 = x + 0
x = 4
For the third row, where y is equal to 7, to find x plug 7 in for y like so...
7 = x - 3
To solve for x add 3 to both sides. This will cancel 3 from the right side:
7 + 3 = x - 3 + 3
10 = x + 0
x = 10
First row: y is 4
Second row: x is 4
Third row: x is 10
Hope this helped!
~Just a girl in love with Shawn Mendes
Which of the following would be the most logical first step to solving this
quadratic equation?
2x2-x+ 2 = -11
O
A. Divide both sides by x.
O
B. Take the square root of both sides.
O
C. Set up smaller equations using the zero product rule.
O
D. Add 11 to both sides.
Answer:
D is correct option
Step-by-step explanation:
The correct option is D.
The standard quadratic equation is ax²+bx+c=0
Where a and b are coefficients and c is constant.
It means that constant are on the L.H.S and there is 0 on the right hand side.
Therefore to make it a quadratic equation first of all you have to add 11 at both sides so that the R.H.S becomes 0.
The given equation is:
2x2-x+ 2 = -11
If we add 11 on both sides the equation will be:
2x2-x+ 2 +11= -11+11
2x^2-x+13=0
Thus the correct option is D
You can further solve it by applying quadratic formula....
Final answer:
The most logical first step to solve the quadratic equation 2x² - x + 2 = -11 is to set up smaller equations using the zero product rule and then applthe quadratic formula. The correct option is c.
Explanation:
The most logical first step to solve the quadratic equation 2x² - x + 2 = -11 is to:
C. Set up smaller equations using the zero product rule.
Once the equation is rearranged, apply the quadratic formula to determine the values of x.
Using the quadratic formula yields the solutions by substituting the values of a, b, and c correctly.
URGENTTTTTTT!!!!!!!!!!
Prove that circle A with center (–1, 1) and radius 1 is similar to circle B with center (–3, 2) and radius 2.
Answer:
Circle A and circle B are similar
Step-by-step explanation:
* Lets explain similarity of circles
- Figures can be proven similar if one, or more, similarity transformations
reflections, translations, rotations, dilations can be found that map one
figure onto another
- To prove all circles are similar, a translation and a scale factor from a
dilation will be found to map one circle onto another
* Lets solve the problem
∵ Circle A has center (-1 , 1) and radius 1
∵ The standard form of the equation of the circle is:
(x - h)² + (y - k)² = r² , where (h , k) are the coordinates the center
and r is the radius
∴ Equation circle A is (x - -1)² + (y - 1)² = (1)²
∴ Equation circle A is (x + 1)² + (y - 1)² = 1
∵ Circle B has center (-3 , 2) and radius 2
∴ Equation circle B is (x - -3)² + (y - 2)² = (2)²
∴ Equation circle B is (x + 3)² + (y - 2)² = 4
- By comparing between the equations of circle A and circle B
# Remember:
- If the function f(x) translated horizontally to the right
by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
- If the function f(x) translated vertically up
by k units, then the new function g(x) = f(x) + k
- If the function f(x) translated vertically down
by k units, then the new function g(x) = f(x) – k
∵ -3 - -1 = -2 and 2 - 1 = 1
∴ The center of circle A moves 2 units to the left and 1 unit up to
have the same center of circle B
∴ Circle A translate 2 units to the left and 1 unit up
∵ The radius of circle A = 1 and the radius of circle B = 2
∴ Circle A dilated by scale factor 2/1 to be circle B
∴ Circle B is the image of circle A after translation 2 units to the left
and 1 unit up followed by dilation with scale factor 2
- By using the 2nd fact above
∴ Circle A and circle B are similar
Find the slope of the line that passes through the points (-1, 1) and (2, 7).
Answer:
2 is your slope
Step-by-step explanation:
Find the slope. Use the slope-formula:
m (slope) = (y₂ - y₁)/(x₂ - x₁)
Let:
(x₁ , y₁) = (-1 , 1)
(x₂ , y₂) = (2 , 7)
Plug in the corresponding numbers to the corresponding variables:
m = (7 - 1)/(2 - (-1))
Simplify:
m = (6)/(2 + 1)
m = 6/3
m = 2
2 is your slope (or rise 2, run 1).
~
Answer:
slope = 2
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 1, 1) and (x₂, y₂ ) = (2, 7)
m = [tex]\frac{7-1}{2+1}[/tex] = [tex]\frac{6}{3}[/tex] = 2
This circle is centered at the point (3, 2), and the length of its radius is 5. What
is the equation of the circle?
Answer:
(x-3)² + (y-2)² = 25
Step-by-step explanation:
A circle's equation is (x-h)² + (y-k)² = r². When centered at the origin, h and k equal 0. If you shift the circle, say, one unit up, then k equals 1, and the equation is x² + (y-1)² = r².
So for your circle, the equation would be (x-3)² + (y-2)² = 5² or (x-3)² + (y-2)² = 25.
what are the zeros of the polynomial function f(x)=x^3-x^2-6x
Answer:
x = -2, x = 0, and x = 3
Step-by-step explanation:
it was right lol
The volume of the spheres is 500/3 pie cubic units What is the value of X?
Answer:
125
Step-by-step explanation:
500 ÷ 4 = 125
I think this is the right answer. sorry if I'm wrong.
Answer:
x=5 assuming that x is the radius.
x is the radius?
Step-by-step explanation:
[tex]V=\frac{4}{3} \pi r^3[/tex] is the volume of a sphere.
We are given [tex]V=\frac{500}{3} \pi[/tex] cubic units.
We are asked to find the value of x. If x is not the radius, please correct me:
[tex]V=\frac{4}{3}\pi r^3[/tex] with [tex]V=\frac{500}{3} \pi[/tex] and the assumption that x is r.
[tex]\frac{500}{3}\pi=\frac{4}{3}\pi x^3[/tex]
If you multiply both sides by 3, then you would have:
[tex]500 \pi=4 \pi x^3[/tex]
If you divide both sides by [tex]\pi[/tex] you will have:
[tex]500=4x^3[/tex]
If you divide both sides by 4, you will have:
[tex]125=x^3[/tex]
The last step would be to take the cube root of both sides:
[tex]\sqrt[3]{125}=x[/tex]
[tex]5=x[/tex]
[tex]x=5[/tex]
Solve 3x − 2 = 37. please help me
To solve the equation 3x - 2 = 37, you add 2 to both sides to get 3x = 39. Then, you divide by 3 to solve for x, obtaining x = 13.
Explanation:To solve the equation
3x − 2 = 37
for x, you start by moving the -2 to the other side of the equation by adding 2 to both sides. This gives you
3x = 39
. Then, you isolate x by dividing every term by 3. After dividing, you find that
x = 13
. So the solution to the equation 3x - 2 = 37 is x = 13.
Learn more about solving equations here:https://brainly.com/question/14410653
#SPJ2
To solve the equation, add 2 to both sides and then divide by 3 to isolate the variable x. The solution is x = 13.
Explanation:To solve the equation 3x - 2 = 37, we need to isolate the variable x. Here are the steps:
Add 2 to both sides of the equation to get rid of the constant term. This gives us 3x = 39.Divide both sides of the equation by 3 to solve for x. This gives us x = 13.Therefore, the solution to the equation is x = 13.
Learn more about Solving Equations here:https://brainly.com/question/14410653
#SPJ12
help with 1-6 , please !!!!!
Answer:
sum of angles of triamgle is 180 degree
the half base× hight ue1/2×b×h
use the formula for all qusetions
If point P is 4/7 of the distance from M to N, what ratio does the point P partition the directed line segment from M to N into?
4:1
4:3
4:7
4:10
Answer:
4:3
Step-by-step explanation:
Given that P divides segment MN into 4/7, let MN to be x units in length then
MP = 4/7 x =4x/7 --------(i)
But MN =MP+PN so;
x=4x/7 +PN
x- 4X/7 =PN
3x/7 =PN ----------(ii)
To get the ratio of MP:PN
MP: PN
4x/7:3x/7
MP/PN = 4x/7 / 3x/7
MP/PN =4/3
MP:PN = 4:3
Answer: 4:3
Step-by-step explanation:
Given : A point P is 4/7 of the distance from M to N.
∴ Let the distance between M to N be d.
[tex]\Rightarrow\ MP=\dfrac{4}{7}\times d=\dfrac{4d}{7}[/tex]
Also, the point P partition the directed line segment from M to N .
Thus , MN = MP+PN
[tex]\Rightarrow\ d=\dfrac{4d}{7}+PN\\\\\Rightarrow\ PN= d-\dfrac{4d}{7}=\dfrac{7d-4d}{7}\\\\\Rightarrow\ PN=\dfrac{3}{7}d[/tex]
Now, the ration of MP to PN will be :-
[tex]\dfrac{MP}{PN}=\dfrac{\dfrac{4d}{7}}{\dfrac{3d}{7}}=\dfrac{4}{3}[/tex]
∴ Point P partitioned the line segment MN into 4:3.
which geometric object is defined as the set of ballpoints in a plane at a given distance A.Parabole B. Line segment C. Line D. circle
Answer:
Answer is Circle
Step-by-step explanation:
Check the picture below.
notice, all points are equidistant from the center of it, wherever the center happens to be.
Expand and simplify (X+5)(X+1)
Answer:
Step-by-step explanation:
(X+5)(X+1) = x²+x+5x+5 = x² +6x+5
(X+5)(X+1)
Use the FOIL method to expand.
This means multiply each term in the first set of parenthesis by each term in the second set.
x *x = x^2
x*1 = x
5*x = 5x
5*1 = 5
Now you have x^2 + x + 5x + 5
Now simplify by combining like terms:
x^2 + 6x + 5
(4^((-11/3))/(4^((-2)/3))
simplify the following expression
Answer:
[tex]\large\boxed{\dfrac{4^{-\frac{11}{3}}}{4^{-\frac{2}{3}}}=\dfrac{1}{64}}[/tex]
Step-by-step explanation:
[tex]\dfrac{4^{-\frac{11}{3}}}{4^{-\frac{2}{3}}}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\=4^{-\frac{11}{3}-\left(-\frac{2}{3}\right)}=4^{-\frac{11}{3}+\frac{2}{3}}=4^{-\frac{9}{3}}=4^{-3}\qquad\text{use}\ a^{-n}=\dfrac{1}{a^n}\\\\=\dfrac{1}{4^3}=\dfrac{1}{64}[/tex]
The simplification of the expression is [tex]\dfrac{1}{64}[/tex].
What are some basic properties of exponentiation?Exponentiation(the process of raising some number to some power) have some basic rules as:
[tex]a^{-b} = \dfrac{1}{a^b}\\\\a^0 = 1 (a \neq 0)\\\\a^1 = a\\\\(a^b)^c = a^{b \times c}\\\\ a^b \times a^c = a^{b+c} \\\\[/tex]
Given ;
[tex]\dfrac{(4^{-11/3})}{(4^{-2/3})}[/tex]
We know that
[tex]\dfrac{a^m}{a^n} = a^{m-n}[/tex]
[tex]\dfrac{(4^{-11/3})}{(4^{-2/3})} = 4^({-11/3 + 2/3})\\\\\\= 4 ^{-9/3}\\\\= 4^{-3}\\\\[/tex]
Hence, [tex]\dfrac{1}{4^3} = \dfrac{1}{64}[/tex]
Learn more about exponentiation here:
https://brainly.com/question/26938318
#SPJ2
Determine algebraically whether f(x) = x^2(x^2 + 9)(x^3 + 2x) is even or odd.
[tex]f(x) = x^2(x^2 + 9)(x^3 + 2x)\\\\f(-x) = (-x)^2((-x)^2 + 9)((-x)^3 + 2\cdot(-x))\\f(-x)=x^2(x^2+9)(-x^3-2x)\\f(-x)=-x^2(x^2+9)(x^3+2x)\\\Large f(-x)\not =f(x)\implies\text{not even}\\\\-f(x)=-x^2(x^2+9)(x^3+2x)\\ -f(x)=f(-x)\implies \text{odd}[/tex]
The value of x is?
84
96
132
264
HELPPPP!!!!
Answer:
x =96 degree.
Step-by-step explanation:
Given : Triangle .
To find : The value of x is
Solution : We have given triangle
Exterior Angle sum property of triangle : Sum of all exterior angle of triangle is 360.
130 + 134 + x = 360 .
264 + x = 360.
On subtracting both sides by 264 .
x = 360 - 264 .
x = 96.
Therefore, x =96 degree.
Using Exterior Angle sum property of the triangle, The value of x will be 96 degree.
What is the Exterior Angle sum property?Exterior Angle sum property of the triangle states that the Sum of all exterior angles of the triangle is 360.
Given: Two exterior angles measure of 130 and 134 degrees.
To find: The value of x is
So,
130 + 134 + x = 360 .
264 + x = 360.
x = 360 - 264 .
x = 96.
Using Exterior Angle sum property of the triangle, The value of x will be 96 degrees.
Learn more about angles here;
https://brainly.com/question/13954458
#SPJ5
Solve the equation over the interval [0,2pi) 4cscx + 6= -2
[tex]\bf 4csc(x)+6=-2\implies 4csc(x)=-8\implies csc(x)=\cfrac{-8}{4}\implies csc(x)=-2 \\\\\\ \cfrac{1}{sin(x)}=-2\implies \cfrac{1}{-2}=sin(x)\implies sin^{-1}\left( -\cfrac{1}{2} \right)=x\implies x= \begin{cases} \frac{7\pi }{6}\\\\ \frac{11\pi }{6} \end{cases}[/tex]
Which of the following equations is of a parabola with a vertex at (0,3)?
y= (x - 3)2
y= (x + 3) 2
y=x2-3
y= x2 + 3
Answer:
[tex]y=x^{2}+3[/tex]
Step-by-step explanation:
we know that
The equation of a vertical parabola in vertex form is equal to
[tex]y=a(x-h)^{2}+k[/tex]
where
(h,k) is the vertex
In this problem we have the vertex at point (0,3)
substitute
[tex]y=a(x-0)^{2}+3[/tex]
[tex]y=ax^{2}+3[/tex]
therefore
The option [tex]y=x^{2}+3[/tex] is the answer
In this case the coefficient a is equal to 1
WILL GIVE BRAINLEIST DUE AT 9:45 P.M. PLS HURRY SUPER EASY. Bella rollerblades 8 miles in one hour. The function rule that represents this situatrion is 8x, where x is the numger of hours. Make a table to find how many hours she had skated when she traveled 16,24, and 32 miles. Then graph the function. After refer to the exercise. How many miles would Bella travel if she skated for 7 hours?
Hours ] 8x ] Miles
? ] ? ] ]
? ] ? ] ]
? ] ? ] ]
Answer:
I hope this helps! <3
Step-by-step explanation:
¿Cuál de las siguientes funciones es una función constante? a. Y=x+1 b. Y=x+2 c. X=y+3 d. Y=3
Answer:
Option D y=3
Step-by-step explanation:
The question in English is
Which of the following functions is a constant function?
we know that
A constant function is a function whose output value is the same for every input value
so
Verify each case
case A) y=x+1
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case B) y=x+2
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case C) x=y+3
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case D) y=3
This is a constant function
Is a function whose output value is the same for every input value
Which of the following expressions are equivalent? Justify your reasoning.
4√x3
1
x−1
10√x5•x4•x2
x
1
3
•x
1
3
•x
1
3
Answer:
b and d
Step-by-step explanation:
b. 1/x^-1
=(1/x)^-1
=x
d. x^1/3 * x^1/3 * x^1/3
=x^1/3+1/3+1/3
=x^3/3
=x^1
=x....
what is the slope intercept equation of the line below
Answer:
y=2x-3
Step-by-step explanation:
The slope-intercept form of a linear equation is y=mx+b where m is the slope and b is the y-intercept.
The y-intercept is where it crosses the y-axis. It cross the y-axis in your picture at -3 so b=-3.
Now the slope=rise/run. So starting at (0,-3) we need to find another point that crosses nicely on the cross-hairs and count the rise to and then the run to it. So I see (1,-1) laying nicely. So the rise is 2 and the run is 1.
If you don't like counting. You could just use the slope formula since we already identified the two points as (-1,1) and (0,-3).
The way I like to use the formula is line up the points and subtract vertically then put 2nd difference over 1st difference.
(0,-3)
-(1,-1)
----------
-1 -2
So the slope is -2/-1 or just 2.
We have that m is 2 and b is -3.
Plug them into y=mx+b and you are done.
y=2x-3.
Slope intercept equation of the line is y = 2x - 3.
What is slope-intercept form?Slope intercept form gives the graph of a straight line and is represented in the form of y=mx + c.
By checking the graph by drawing manually.
From that we get the equation
y = 2x - 3
Comparing above equation with the standard slope-intercept form y = mx +c, we get
Slope : m = 2
Now, given equation can be re-written as :
2x - y = 3
Divide by 3 on both sides
[tex]\frac{2x}{3} -\frac{y}{3} =\frac{3}{3}[/tex]
[tex]\frac{x}{\frac{3}{2} } -\frac{y}{3} =1[/tex]
Comparing above equation with intercept form:
[tex]\frac{x}{a}+\frac{y}{b}=1[/tex], we get
x-intercept : [tex]a=\frac{3}{2}[/tex]
y-intercept : [tex]b=-3[/tex]
Now the given straight line intersects the coordinate axes at [tex](\frac{3}{2} ,0)[/tex] and [tex](0,-3)[/tex]. Specify these plots on XY-plane & join by a straight line to get a plot.
Find out more information about slope-intercept form here
https://brainly.com/question/9682526
#SPJ2
A pathway divides a rectangular garden into two parts as shown. Find the measure of angle A
Answer:
m < A = 101 degrees.
Step-by-step explanation:
The transverse line crosses 2 parallel lines (opposite angles of a rectangle are parallel) , so the same side angles add up to 180 degrees.
m < A + 79 = 180
m < A = 101 degrees.
Answer:
A=101°
Step-by-step explanation:
The two lengths of the rectangle are parallel and therefore the sides of the path form two parallel transversals.
The angle marked 79° and the angle marked A are supplementary ( they add up to 180°)
A+79=180°
A=180-79
=101°
Write a function rule for the table
For this case we must construct a function of the form [tex]y = f (x)[/tex] taking as reference the values of the table.
It is observed that if we evaluate the following function we have:
[tex]f (x) = x + 4[/tex]
Different signs are subtracted and the sign of the major is placed.
[tex]f (-3) = - 3 + 4 = 1\\f (-2) = - 2 + 4 = 2\\f (-1) = - 1 + 4 = 3\\f (0) = 0 + 4 = 4[/tex]
So, the function is:[tex]f (x) = x + 4[/tex]
Answer:
[tex]f (x) = x + 4[/tex]